A THE IMPORTANCE OF DEVELOPING STUDENTS CRITICAL THINKING SKILLS IN THE LEARNING PROCESS - Kholmurodova, Kholmurodova (Журнал иностранных языков и лингвистики, 2022)
The article deals with the ways of developing students’ critical thinking skills and its efficiency in learning process. Critical thinking is significant in the learning process of internalization, in the construction of basic ideas, principles, and theories inherent in content.